IMPLEMENTATION OF THE QUIZIZZ METHOD IN ENHANCING STUDENTS’ LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION (PAI) FOR CLASS X.11 AT SMAN 3 PURWAKARTA - Nursyifa, Siti Hamida; Megawati, Irma (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Learning media plays a crucial role in both conventional and digital teaching and learning processes. In today's digital era, digital platforms offer significant potential for improving the quality of Islamic Religious Education (PAI) learning, yet their utilization at SMAN 3 Purwakarta is not yet optimal. This study aims to analyze the use of digital platforms in Islamic Religious Education (PAI) learning at the school, identify the challenges and opportunities faced, and formulate recommendations for increasing their effectiveness. The research methods used were direct observation, interviews, and documentation studies. The results indicate that although digital platforms have significant potential to make Islamic Religious Education (PAI) learning more engaging, interactive, and effective, obstacles remain, such as a lack of digital literacy among teachers and students, and suboptimal utilization of digital platform features. This study also identifies opportunities to enhance the use of digital platforms in Islamic Religious Education (PAI) learning, such as training, digital literacy, the development of engaging digital learning content, and the use of digital platforms for learning evaluation. Based on the research findings, recommendations are formulated, which are expected to provide input for teachers, schools, and digital platform developers to improve the quality of Islamic Religious Education (PAI) learning in the digital era.